PERISTILAHAN DALAM PROSESI TEMU MANTEN PADA MASYARAKAT JAWA DI DESA PARIT KELADI KECAMATAN SUNGAI KAKAP - Herawati Herawati; Hotma Simanjuntak; Patriantoro Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the terminology in the Temu Manten procession in the Javanese community in Parit Keladi Village, Sungai Kakap District. The problem of this research is the form of terminology, lexical meaning, grammatical meaning, cultural meaning and the implementation of terminology in the Temu Manten procession in the Javanese community in Parit Keladi Village, Sungai Kakap District on learning at school. This research uses descriptive method in the form of qualitative. Data collection techniques, namely, observation, interview, note and record. This study resulted in 53 linguistic data in the Temu Manten procession in the Javanese community in Parit Keladi Village, Sungai Kakap District which consisted of the term tool containing 9 data, the term material 27 data, the term cultural object 2 data, the term actor 8 data, and the term procession 7 data. . The form of terminology in the form of monomorphism contained 26 data, reduplication contained 2 data, and phrases contained 25 data. The meaning contained in the term temu manten procession in the Javanese community in Parit Keladi Village, Sungai Kakap District, is based on the lexical meaning of 39 data, the grammatical meaning of 23 data and the cultural meaning of 47 data. The form of the Indonesian language learning text based on the terminology in the Temu Manten procession in the Javanese community in Parit Keladi Village, Sungai Kakap District is a descriptive text.